Evaluation of Improved Maize Populations and Their Diallel Crosses for Yield - Sansern Jampatong; Manasanan Thung-Ngean; Chatpong Balla; Prapon Boonrumpun; Anucha Mekarun; Choosak Jompuk; Rungsarid Kaveeta (Agriculture and Natural Resources, 2010)
Broadening the genetic base and increasing the yield potential of maize breeding populations are of prime importance to maize breeders. One potential source is the use of exotic germplasm by incorporating exotic sources into adapted sources. The objective of this study was to evaluate the breeding potential of ten maize populations for the hybrid breeding program. Ten breeding populations, diallel crosses among the populations, and nine check hybrids were evaluated in 2008, using an 8 × 8 triple lattice at three locations. Sources of variation for entries, populations, general combining ability (GCA) and specific combining ability (SCA) were highly significant. KS23(S)C5 had the highest positive significant GCA and variety effects of all the populations tested. Suwan1(S)C14 × KS23(S)C5 had the highest yield (8.27 Mg ha-1) with high-parent heterosis of 14.23%. KS23(S)C5 was also among the parents of the other top three high-yielding crosses: KS23(S)C5 × KS24(S)C3 (8.09 Mg ha-1), KS6(S)C4 × KS23(S)C5 (7.79 Mg ha-1), and KS23(S)C5 × KS28(S)C2 (7.75 Mg ha-1). From the results, KS6(S)C4 × KS28(S)C2 had the highest high-parent heterosis (17.17%) with a yield of 7.44 Mg ha-1. KS23 was superior to the other introgressed exotic maize populations and it seemed to be a new potential source in crosses with Suwan1 and derivatives of Suwan1 for the hybrid maize breeding program.